USE OF TEACHING METHODS FOR YOUNG LEARNERS BY TEACHER OF BRITON ENGLISH EDUCATION MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2023)
The aim of this research was to find out teaching methods used by the teacher of Briton English Education Makassar in teaching English for young learners and to investigate the reason of the English teacher of Briton English Education Makassar using the methods. In conducting this research, the researcher used descriptive-qualitative research. Observation and interview were the techniques to collect the data. The finding of this research indicated that the teacher of Briton English Education Makassar used five methods to teach English for young learners especially on flyers level. The five methods were natural approach method, audio-lingualism method/army method, question-answer method, playing method and demonstration method. The teacher’s reason of using the five methods was because the teacher considered that the methods were the most suitable methods used to teach English for the students on flyers level.